Post-traumatic stress disorder and cardiometabolic disease: improving causal inference to inform practice - Koenen, K. C.; Sumner, J. A.; Gilsanz, P.; Glymour, M. M.; Ratanatharathorn, A.; Rimm, E. B.; Roberts, A. L.; Winning, A.; Kubzansky, L. D. (Psychological medicine, 2017)
Post-traumatic stress disorder (PTSD) has been declared ‘a life sentence’ based on evidence that the disorder leads to a host of physical health problems. Some of the strongest empirical research – in terms of methodology and findings – has shown that PTSD predicts higher risk of cardiometabolic diseases, specifically cardiovascular disease (CVD) and type 2 diabetes (T2D). Despite mounting evidence, PTSD is not currently acknowledged as a risk factor by cardiovascular or endocrinological medicine. This view is unlikely to change absent compelling evidence that PTSD causally contributes to cardiometabolic disease. This review suggests that with developments in methods for epidemiological research and the rapidly expanding knowledge of the behavioral and biological effects of PTSD the field is poised to provide more definitive answers to questions of causality. First, we discuss methods to improve causal inference using the observational data most often used in studies of PTSD and health, with particular reference to issues of temporality and confounding. Second, we consider recent work linking PTSD with specific behaviors and biological processes, and evaluate whether these may plausibly serve as mechanisms by which PTSD leads to cardiometabolic disease. Third, we evaluate how looking more comprehensively into the PTSD phenotype provides insight into whether specific aspects of PTSD phenomenology are particularly relevant to cardiometabolic disease. Finally, we discuss new areas of research that are feasible and could enhance understanding of the PTSD–cardiometabolic relationship, such as testing whether treatment of PTSD can halt or even reverse the cardiometabolic risk factors causally related to CVD and T2D.